Trends and demographic differences in interpersonal violence against children in sub-Saharan Africa: findings from the 1990–2019 Global Burden of Disease Study - Nhassengo, Sergio; Laflamme, Lucie; Sengoelge, Mathilde; Nhassengo, Sergio Keita; Abate, Yohannes Habtegiorgis; Abebe, Mesfin; Abegaz, Kedir Hussein; Abiodun, Olumide; Aboagye, Richard Gyan; Adde, Kenneth Setorwu; Adeagbo, Oluwafemi Atanda; Adepoju, Abiola Victor; et al. (BMJ open, 2025)
ObjectivesTo analyse the past 30-year trends in mortality and morbidity of interpersonal violence against children, its demographic distribution and correlation with specific risk factors.DesignEcological study at the country and regional level.Setting46 countries and 4 subregions of sub-Saharan Africa (SSA): Central, Eastern, Southern and Western.ParticipantsChildren aged 0–19 years old.Primary and secondary outcome measuresTrends in mortality rates and disability-adjusted life-years (DALYs) attributed to interpersonal violence injuries in children; correlation between socio-demographic index (SDI)/alcohol consumption per capita and child interpersonal violence.ResultsDeaths and DALYs per 100 000 population from child violence-related injuries in SSA declined from 4.0 (95% uncertainty interval (UI): 3.3–4.9) to 3.1 (95% UI: 2.3 to 3.9) and 334.9 (95% UI: 276.4 to 407.7) to 260.3 (95% UI: 197.9 to 321.9) respectively from 1990 to 2019 (reductions of 22.5% and 22.3%). Southern SSA had the highest deaths/DALYs rates for each type of physical violence (sharp object/firearm/other) and Central SSA for sexual violence. Alcohol consumption correlated significantly with deaths and DALYs, but SDI showed a non-significant correlation.ConclusionsRates of child interpersonal violence deaths and DALYs decreased from 2009 to 2019 in SSA, driven by remarkable decreases in the Southern subregion. Understanding the determinants of these downward trends and implementation of policies targeting known risk factors like alcohol consumption may pave the way for enhanced child safety protection. Further curbing the disparities between countries and subregions necessitates long-term commitment to evidence-based action plans.